Desenvolvimento de circuitos equivalentes para o cálculo de faltas simultâneas na mesma localidade com modelagem em componentes simétricas - Fernandes Filho, Antonio Marcos (Universidade Federal Rural do Semi-Árido, 2019)
This work presents new equations and new equivalent circuits in symmetrical components for the calculation of simultaneous faults, that involves two faults which occurs simultaneously. The symmetrical components can be used for the calculation of voltages and currents in balanced and unbalanced electrical systems, from the decomposition into three balanced systems (sequences zero, positive and negative), moreover one of the main applications is the calculation of fault currents and voltages. As in the classical power systems analysis literature there are equivalent circuits for the calculation of faults like three phase, single line to ground, line to line and line to line to ground, it’s also possible to develop equivalent circuits for simultaneous fault, like double single line to ground (phase A), double line to line (phases AB and AC), single line to ground and line to line to ground (phases A and BC) and single line to ground and line to line (phases A and BC), etc. After obtaining each of the new equivalent circuits, the demonstration of the analytical applicability of the developed models was made through a didactic example in a small system. For the validation of the models developed, a comparison was made between the results obtained from the equivalent circuits and the output of commercial software ANAFAS. Finally, it is proposed the integration of the models developed in short-circuit theory
Keywords: Componentes simétricas; Curto-circuito; Faltas simultâneas; Circuito equivalente; Symmetrical components; Short-circuit; Simultaneous fault; Equivalent circuits; ENGENHARIAS::ENGENHARIA ELETRICA